مهارات فعالية الحياة لدى طلبة جامعة الوادي - ضو, الزهرة (University of Eloued جامعة الوادي, 2023)
ملخص الدراسة: تناولت الدراسة الحالية موضوعا هاما حول مهارات فعالية الحياة لدى الطلبة الجامعيين، والهدف منها هو الكشف عن مستوى مهارات فعالية الحياة لدى طلبة جامعة الوادي، ومعرفة الاختلافات في مستوى المهارات وفق عدة متغيرات منها: الجنس، والتخصص الدراسي، والمستوى التعليمي. وقد تمحورت الدراسة حول التساؤلات التالية: 1- ما مستوى مهارات فعالية الحياة لدى طلبة الجامعة؟ 2- هل توجد فروق في مستوى مهارات فعالية الحياة لدى طلبة الجامعة باختلاف الجنس؟ 3- هل توجد فروق في مستوى مهارات فعالية الحياة لدى طلبة الجامعة باختلاف التخصص الدراسي؟ 4- هل توجد فروق في مستوى مهارات فعالية الحياة لدى طلبة الجامعة باختلاف مستواهم التعليمي؟ تمت الدراسة وفق المنهج الوصفي القائم على الاستكشاف والمقارنة، واختيرت العينة من طلبة جامعة الوادي بطريقة عشوائية طبقية، وتكونت العينة من (100) طالب وطالبة. تمثلت أداة الدراسة في استبيان يقيس مهارات فعالية الحياة، يتضمن (40) بندا مفاده معرفة مستوى مهارات فعالية الحياة لدى الطلبة الجامعيين، وقد توصلت الدراسة إلى النتائج التالية: - مستوى مهارات فعالية الحياة مرتفع لدى طلبة جامعة الوادي. - لا توجد فروق ذات دلالة إحصائية في مستوى مهارات فعالية الحياة لدى طلبة الجامعة باختلاف جنسهم. - لاتوجد فروق ذات دلالة إحصائية في مستوى مهارات فعالية الحياة لدى طلبة الجامعة باختلاف تخصصهم الدراسي. - توجد فروق ذات دلالة إحصائية في مستوى مهارات فعالية الحياة لدى طلبة الجامعة باختلاف مستواهم التعليمي لصالح طلبة الماستر. Abstract: The current study dealt with an important topic about life effectiveness skills among university 's students, and the aim is to reveal the level of life effectiveness skills among students and to identify the differences in the skills' level according to many variables including gender, academic specialization and educational level. The study focused on the following questions: 1- What is the level of life's effectiveness skills among university students? 2- Are there differences in the level of life's effectiveness skills among university students according to gender (male - female) 3- Are there differences in the level of life's effectiveness skills among university students according to difference academic specialization? 4- Are there differences in the level of life's effectiveness skills among university students according to their variable educational level? The study had carried out by using the descriptive, exploratory approach based on comparison and the sample was selected from university students in the valley in a stratified manner, and the sample consisted of 100 students. The tool of study was a questionnaire that measures life effectiveness skills and includes 40 items to know the level of life's effectiveness skills of university students. The study found the following results: - The level of life's effectiveness skills is high among university students. - There are no statistically significant differences in the level of life's effectiveness skills of university students between males and females. - There are statistically significant differences in the level of life's effectiveness skills among university students, despite the difference in academic specialization. - There are statistically significant differences in the level of life's effectiveness skills among university students according to the educational level in favor of master's students.
تخصص ارشاد و توجيه